البناء الفنّي للقصّة القصيرة جدّا في المغرب العربي –نماذج منتخبة- - شابي منيرة (My University, 2025)
Abstract This research explores the artistic structure of the very short story in the Maghreb region, through an analytical study of selected models from Morocco,Algeria, and Tunisia.The study aims to uncover the narrative techniques and aesthetic characteristics that define this emerging literary genre,focusing on symbolic,stylistic,and sematic aspects. -The research analyzes how Maghrebi authors use interextuality, irony, compression, and linguistic condensation to build dense texts with deep meanings.It also compares stylistic specificities across the three national experiences. -Furthermore,the study tracks the evolution of this genre in both Arab and global contexts,examinning its independence from tradional short stories and its ability to reflect contemporary realities through minimalist language and high-impact expression. -This work contributes to the critical foudation of the very short story genre by highlighting its artistic richness and expressive diversity within the Maghreb literary space ---------------------- تتناول هذه المذكرة موضوع البناء الفني للقصة القصيرة جدا في المغرب العربي، من خلال دراسة تحليلية لنماذج مختارة من المغرب، الجزائر و تونس. تسعى الدراسة الى الكشف عن السمات الجمالية و التقنيات السردية التي تميز هذا الجنس الأدبي الجديد عبر تحليل النصوص في أبعادها الأسلوبية و الدلالية و الرمزية. -ركز البحث على كيفية توظيف التناص، المفارقة ، الاختزال ، و تكثيف اللغة من طرف الكتاب المغاربيين، و استجلاء البنية العميقة للنصوص، من حيث الشكل و المحتوى. -كما هدفت المذكرة الى تتبع نشأة هذا الجنس الأدبي و تطوره في الوطن العربي و العالم، و تبيان مدى استقلاليته عن القصة القصيرة ، و قدرته عللى التعبير عن تحولات الواقع في لغة مكثفة و بلاغة موجزة . - تعد هذه الدراسة مساهمة في التأصيل النقدي لهذا الجنس، من خلال رصد تجلياته الفنية و تحليل نماذجه الرائدة ، مما يبرز غنا الرمزي و تنوعه التعبيري داخل الفضاء المغاربي. ------------------------ - Ce memoire traite de la structure artistique de la très courte nouvelle au Maghreb, à travers une etude analytique de modèles choisis provenant du Maroc, de l' Algerie et de la Tunisie. L'objectif est de mettre en lumiere les caractèristiques esthètiques et les techniquesnarratives qui dèfinissent ce genre littèraire èmergent, en insistant sur ses dimentions symboliques, stylistiques et sèmantiques. - L'analyse se penche sur la maniéredont les auteurs maghrèbins mobilisent le tressage intertextuel, l'ironie, la concision et l'économie du langage pour produire des textes denses et signifiants.Une comparaison stylistique est également menée entre les expériences nationales. -Le travail retrace aussi l'évolution de ce genre à l'échelle arabe et mondiale, en questinnant son autonomie par rapport à la nouvelle traditionnelle et sa capacitè à exprimer les mutations du réel avec un language minimaliste et une esthétique de l'ellipse. -Cette recherche constitue une contribution à l'ancrage critique de la trés courte nouvelle en soulignant sa richesse symbolique et sa diversité expressive dans l'espace littéraire maghrébin.
Keywords: القصة القصيرة جدا، البناء الفني، العناصر الفنية، السرد القصصي; La microfiction; la structure artistique; les éléments narratifs; la narration; Flash fiction; artistic structure. Narrative elements; strytelling